A REVIEW OF AGRICULTURAL AND COASTAL CITIES IN INDONESIA IN FINDING URBAN SPRAWL PRIORITY PARAMETERS - Stivani Ayuning Suwarlan; Lee Yoke Lai; Ismail Said (architecture department, Engineering faculty, Universitas Diponegoro, 2022)
Urban sprawl has caused an impact on urban development, causing land use changes, loss of income and cultural values, environmental degradation, and high monetary costs. Urban sprawl needs to be carried out efficiently and inclusively to ensure sustainable land use and management including cities in Indonesia. Since 1980s, urban sprawl in Indonesia is high due to limited land which causes the expansion of development on the expanse of agricultural areas and coastal settlements. This paper presents a critical review of the parameters of urban sprawl in agricultural cities including Bandung, Batu, Pekanbaru and coastal cities including Surabaya, Gresik, and Madura using the Analytic Hierarchy Process (AHP). The parameters are gathered from a review of articles related to urban sprawl in agricultural and coastal cities in Indonesia. The result of this comparative studies showed two key important variables that caused urban sprawl in Indonesia: population growth, and land limitation to encompass agricultural and coastal cities. Furthermore, there are four priority parameters out of eight, namely immigrant population ratio-transnational, birth ratio, population growth rate, and land occupation ratio causing urban sprawl in agricultural and coastal cities. In sum, the findings of this study suggest the importance of applying urban sprawl parameters in analyzing urban development as it is useful for evaluating and monitoring the rapid urban development in Indonesia.